Algerian youth between job insecurity and occupational instability - Bounouiga , Nacera; Boudjellal , mostefa (Journal of Social Sciences and Humanities, 2021)
The priorities and needs for young people who want the job to satisfy their material needs, they express job security from a purely economic perspective, and those who are primarily interested in giving them the right position regardless of the factors of profit and loss reflect job security from a perspective social. In the light of the dimensions that reflect the importance of job security for young people; from the sense of security and stability, job security is achieved only when the job fills the natural needs and social needs, and begins to feel the security of the highest levels of the job when the job fills the need for appreciation and respect for what the young man The employee or the worker in an effort to perform his functions. There are things that the young worker may encounter in the course of his job. He expects that experience and gain will help him to obtain a higher position or job within the institution and enough money to secure a decent life for him and his family, The confidence, calmness and motivation that job security brings to young people help to carry out the workload and face problems effectively. A young man who is not stable due to lack of job security or low level of job security is less capable of good professional stability or facing contemporary problems that require innovative methods and solutions. But radical changes, such as industrial restructuring, new information technology, intense global competition, and flexible labor contracts have all contributed to creating a sense of job insecurity for young people.